Catalysis without precious metals - Bullock, R. Morris (Wiley-VCH, 2010)
Written for chemists in industry and academia, this ready reference and handbook summarizes recent progress in the development of new catalysts that do not require precious metals. The research thus presented points the way to how new catalysts may ultimately supplant the use of precious metals in some types of reactions, while highlighting the remaining challenges. An essential companion for organic and catalytic chemists, as well as those working with/on organometallics, and graduate students.